2001
DOI: 10.1016/s0736-5748(00)00070-8
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal stress and postnatal development of neonatal rats — sex‐dependent effects on emotional behavior and learning ability of neonatal rats

Abstract: Maternal sound stress (800 Hz; 77 dB, every other minute for 15 min/day, from day 10 to 18 of gestation), combined with forced swimming stress (15 min/day), was found to cause potentiation of sound-induced loss of locomotor activity, referred to as emotional behavior, of male offspring, but not that of female offspring, at 4 weeks of age. Maternal stress also caused an increase in the total number of errors by male, but not female offspring in the water-maze test at 6 weeks of age. These effects of stress on e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
2
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(47 citation statements)
references
References 14 publications
2
42
2
1
Order By: Relevance
“…Adult PS rats, mainly the male but not female offspring, spent more time searching for the platform location in a watermaze task, when the water is kept at 121C (Szuran et al, 1994). This observation was recently extended by Nishio et al (2001) who reported that rats, prenatally stressed using a sound stress, exhibit an increased in total number of errors in the water-maze and time spent searching for the platform location. Lordi et al (1997) also previously described that adult PS rats are impaired for delayed alternation behavior, with an ITI of 1 h but not with an ITI of 30 s or 3 min, and in a passive avoidance response.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Adult PS rats, mainly the male but not female offspring, spent more time searching for the platform location in a watermaze task, when the water is kept at 121C (Szuran et al, 1994). This observation was recently extended by Nishio et al (2001) who reported that rats, prenatally stressed using a sound stress, exhibit an increased in total number of errors in the water-maze and time spent searching for the platform location. Lordi et al (1997) also previously described that adult PS rats are impaired for delayed alternation behavior, with an ITI of 1 h but not with an ITI of 30 s or 3 min, and in a passive avoidance response.…”
Section: Discussionmentioning
confidence: 87%
“…Szuran et al (1994) reported that PS rats submitted to place learning in the water-maze fail to show any deficit when the water temperature was kept at 181C, while female, but not male, PS rats show significant deficits when the water was cooled to 121C. Nishio et al (2001) reported that a maternal sound stress combined with a forced swimming stress potentiates the sound-induced loss of locomotor activity in male, but not female, PS offspring rats. In addition, an increase in the number of errors in the water-maze is measured only for male PS rats (Nishio et al, 2001).…”
Section: J Meunier Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…These results were comparable to those which we found in the effects of prenatal stress applied to the pregnant rats on the emotional behavior and learning ability of offspring. 7) It is interesting to note that when the stress was applied immediately after weaning, 3 weeks after birth, the mice did not show any changes in the emotion-related behavior during the adolescent period. Lately, Matsumoto et al 9) reported the alteration of the neuronal modulation to emotional stress by early postnatal stress during the postadolescent periods of rats.…”
Section: Discussionmentioning
confidence: 97%
“…We have reported that the sound noise and forced swim stress, applied to pregnant rats, induced changes in the emotional behavior and learning ability of the neonatal rats. 7) This disparity between mice and rats might be explained by the suggestion that the critical period of the brain functional development is dissimilar between these animals. 8) In conformity to these experimental results, we evaluated the effects of postnatal stress to observe the possible influence of stress on the mouse brain functional development.…”
Section: Discussionmentioning
confidence: 99%